Possible Negative Ultra-Short Loop Feedback of Luteinizing Hormone Releasing Hormone (LHRH) in the Ovariectomized Rat - de Castro, J.C. Bedran; Khorram, O.; Mccann, S. M. (Frontiers, 1985)
To determine if LHRH might act within the brain to modify its own release, repeated blood samples were removed from conscious ovariectomized rats and minute doses of LHRH were injected into the third ventricle (3V). The effect of these injections on plasma LH and FSH was measured by radioimmunoassay (RIA). The higher dose of intraventricular LHRH (10 ng in 2 yl) induced an increase in plasma LH within 10 min after its injection. Plasma LH decreased for the next 60 min. This was followed by restoration of LH pulses characteristic of the ovariectomized rat. This dose of LHRH slightly elevated plasma FSH concentrations. In stark contrast, a 10 fold lower dose of 1 ng of LHRH injected into the ventricle resulted in a highly significant decrease of plasma LH at 10 min following injection, followed by return of LH pulsations. There was no effect on the pulsatile release of FSH. The results are interpreted to mean that at the higher dose, sufficient LHRH reached the site of origin of the hypophyseal portal vessels in the median eminence so that it diffused into portal vessels and was delivered to the gonadotrophs to induce LH release. In contrast, the lower dose provided sufficient hypothalamic concentrations of the peptide to suppress the discharge of the LHRH neurons, thereby leading to a decline in plasma LH, indicative of an ultrashort-loop negative feedback of LHRH to suppress its own release. © 1985, SAGE Publications. All rights reserved.